Variation of malaria transmission and morbidity with altitude in Tanzania and with introduction of alphacypermethrin treated nets - Magogo Frank (Malaria Journal, 2003)
Abstract Background Highland areas with naturally less intense malaria transmission may provide models of how lowland areas might become if transmission was permanently reduced by sustained vector control. It has been argued that vector control should not be attempted in areas of intense transmission. Methods Mosquitoes were sampled with light traps, pyrethrum spray and window exit traps. They were tested by ELISA for sporozoites. Incidence of malaria infection was measured by clearing existing infections from children with chlorproguanil-dapsone and then taking weekly blood samples. Prevalence of malaria infection and fever, anaemia and splenomegaly were measured in children of different age groups. All these measurements were made in highland and lowland areas of Tanzania before and after provision of bednets treated with alphacypermethrin. Results Entomological inoculation rates (EIR) were about 17 times greater in a lowland than a highland area, but incidence of infection only differed by about 2.5 times. Malaria morbidity was significantly less prevalent in the highlands than the lowlands. Treated nets in the highlands and lowlands led to 69–75% reduction in EIR. Malaria morbidity showed significant decline in younger children at both altitudes after introduction of treated nets. In children aged 6–12 the decline was only significant in the highlands Conclusions There was no evidence that the health benefits to young children due to the nets in the lowlands were "paid for" by poorer health later in life. Our data support the idea of universal provision of treated nets, not a focus on areas of natural hypo-endemicity.